Civilization and Culture: Reevaluating the Relationship between Civilization and Culture (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article discusses  the historical  usages  of  “civilization” and “culture”  and   various   definitions  advanced   by   thinkers  such   as Oswald Spengler, FernandBraudel, and Philip  Bagby, while alsosuggesting a new way of dealing with these two terms. The argument is that “civilization” is the key term todenote  groups and peoples who share alarge and common geographic locus, values and social institutions, and that“culture” refers to a particular set of  values   or   beliefs  within   the   larger  historico-cultural   entity   that is a civilization. If we treat “civilization” as the largest and highest socio -historical unit   and  “culture”   as   something   smaller,   lower,   and  subsumed  under “civilization,” wewill better  understand the ubiquitousphenomenon of cultural appropriation and civilizational hybridization. To further elucidate how these two terms  should be understood and to disentangle themfrom each other, the essay provides an historical account of the context inwhich each term arose.